Patterns of Temperature and Water Level in a Small Mesotidal Estuary: The Case of Ria de Alvor (Portugal) - Rita Novo; Nuno Vaz; Sofia Bartolomeu; Ana Picado; João Miguel Dias; Paulo Chambel Leitão (Journal of Marine Science and Engineering)
Simulating present status and future changes in water level and water temperature in estuaries is important for the advancement of knowledge and decision-making on subjects such as estuarine dynamics and human activities since these variables impact biochemical variables (e.g., oxygen and pH), fish growth, and disease occurrence. Numerical models such as MOHID—Water Modeling System can be used to predict water temperature and water levels under different force conditions. This study evaluates the effects of sea level rise (SLR), air temperatures, and freshwater discharge on water levels and water temperature in the Ria de Alvor under present and future variations. The results show a significant impact of SLR on water levels in the Ria de Alvor, which is more pronounced during spring tides. Air temperature also impacts water temperature, generating changes higher than 2 °C inside the estuary. The freshwater discharge, despite the relatively low values, contributes significantly to changes in surface water temperature, mainly at the estuary’s upper reaches, where it contributes to a decrease in water temperature in winter conditions while elevating them during the summer. The results contribute to the advancement of knowledge on a small, barely studied estuarine system, giving insights into the establishment of human activities such as aquaculture exploitation within the estuary.